Landau-Kleffner Syndrome: Course and Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The presentation, course and outcome of Landau-Kleffner syndrome (LKS) were studied in 18 children (11 girls, 7 boys) followed for a mean of 67 months at Guy's Hospital, London, UK.